2022
DOI: 10.1101/2022.01.23.477397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ronapreve (REGN-CoV; casirivimab and imdevimab) reduces the viral burden and alters the pulmonary response to the SARS-CoV-2 Delta variant (B.1.617.2) in K18-hACE2 mice using an experimental design reflective of a treatment use case

Abstract: The Omicron variant (B.1.1.529) of SARS-CoV-2 has placed enormous strain on global healthcare systems since it was first identified by South African researchers in late 2021. Omicron has >50 mutations which mainly occur in the surface spike protein and this has led to rapid assessment of monoclonal antibodies to assess the impact on virus neutralisation. Ronapreve has shown potential application in post-exposure prophylaxis, mild/moderate disease and in seronegative patients with severe COVID19, but several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In vitro assays with pseudoviruses 5 and authentic viruses 1 established that mAb therapies from Regeneron (REGN10933 and REGN10987), Lilly (LY-CoV555 and LY-CoV016), and Celltrion (CT-P59) showed a complete loss in neutralizing activity against BA.1. Subsequent experiments in K18-hACE2 mice confirmed that the REGN-COV2 mAb cocktail completely lost its efficacy against the BA.1 variant 21 . More recently, an additional antibody (LY-CoV1404, bebtelovimab), which shows considerable neutralization activity against a range of SARS-CoV-2 strains, received EUA status 22 , although protection data in vivo against VOC, including Omicron, has not yet been published.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro assays with pseudoviruses 5 and authentic viruses 1 established that mAb therapies from Regeneron (REGN10933 and REGN10987), Lilly (LY-CoV555 and LY-CoV016), and Celltrion (CT-P59) showed a complete loss in neutralizing activity against BA.1. Subsequent experiments in K18-hACE2 mice confirmed that the REGN-COV2 mAb cocktail completely lost its efficacy against the BA.1 variant 21 . More recently, an additional antibody (LY-CoV1404, bebtelovimab), which shows considerable neutralization activity against a range of SARS-CoV-2 strains, received EUA status 22 , although protection data in vivo against VOC, including Omicron, has not yet been published.…”
Section: Discussionmentioning
confidence: 93%
“…However, demonstrating this in SARS-CoV-2 clinical trials will be difficult because of the hesitancy to use drugs with reduced in vitro activity in a clinical trial and because of the rapidly changing spectrum of circulating SARS-CoV-2 variants. Considering the reduced activity of both sotrovimab and cilgavimab/tixagevimab against Omicron in vitro and the difficulty in performing variant-specific clinical trials, the efficacy of these mAbs against Omicron should be assessed in animal models as has been done for casirivimab/imdevimab [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Regeneron MAbs Casirivimab (REGN10933) and Imdevimab (REGN10987) are absolutely knocked out by the Omicron variant ( 47 ), and their activity of neutralizing the Omicron variant is lost ( 49 , 81 ), even at the highest concentration ( 82 ). At doses 2-fold greater than those demonstrated to be active against prior variants of the virus, Ronapreve reduced subgenomic RNA in lung and nasal turbinates of in K18-hACE2 mice only for the Delta variant but not the Omicron variant ( 83 ). These findings contribute to the growing evidence suggesting effectiveness of Ronapreve is impaired in the Omicron variant ( 83 ).…”
Section: Resistance Of the Omicron Variant To Therapeutic Monoclonal ...mentioning
confidence: 93%
“…At doses 2-fold greater than those demonstrated to be active against prior variants of the virus, Ronapreve reduced subgenomic RNA in lung and nasal turbinates of in K18-hACE2 mice only for the Delta variant but not the Omicron variant ( 83 ). These findings contribute to the growing evidence suggesting effectiveness of Ronapreve is impaired in the Omicron variant ( 83 ). Similarly, the Omicron variant is completely resistant to the Eli Lilly MAbs Bamlanivimab (LY-CoV555) and Etesevimab (LY-CoV016) ( 47 , 49 ).…”
Section: Resistance Of the Omicron Variant To Therapeutic Monoclonal ...mentioning
confidence: 93%